Associations between socioeconomic status and cardiovascular risk factors in an urban population in China - Zhijie Yu; Aulikki Nissinen; Erkki Vartiainen; Guide Song; Zeyu Guo; Gengwen Zheng; Jaakko Tuomilehto; Huiguang Tian (The World Health Organization, 2000)
INTRODUCTIONS: In developed countries socioeconomic status has been proven to be an important factor in the progression of cardiovascular disease. The present article reports the results of a cross-sectional assessment to investigate the association between socioeconomic status and cardiovascular risk factors in a Chinese urban population. METHODS: In 1996, a behavioural risk factor survey was carried out in Tianjin, the third largest city in China. A sample of 4000 people aged 15-69 years, stratified by sex and 10-year age groups, was drawn randomly from urban areas of the city. The present study covers respondents aged 25-69 years (1615 men and 1592 women). Four socioeconomic indicators (education, occupation, income, and marital status), blood pressure, body mass index, and cigarette smoking were determined in the survey. RESULTS: Educational level seemed to be the most important measure of the four socioeconomic indicators in relation to the cardiovascular risk factors in the study population. People with lower socioeconomic status had higher levels of cardiovascular risk factors. The association between socioeconomic status and cardiovascular risk factors was more consistent among women than men. DISCUSSION: Our findings do not seem to differ from those observed in developed countries.